Meningkatkan kinerja pelayanan publik dalam pencegahan kekerasan terhadap perempuan dan anak di kelurahan - Fauzan, Rofik (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Violence against women and children is still frequently encountered in the midst of modern society today. According to data from 2023 in Semarang City, there were 226 cases of violence, with 152 of them occurring within households. The purpose of this research is to provide education to the community regarding the root causes of unlawful actions commonly observed within households, pertaining to both women and children, and to suggest preventive measures to avoid such incidents. The methodology involves surveys, in-depth interviews, and document analysis to understand the challenges, needs, and expectations of the community regarding public services at the neighborhood level in order to develop preventive measures against violence towards women and children. The analysis reveals that incidents indicating non-respectful treatment towards women and children still occur in society, alongside a lack of understanding among residents regarding violence against women and children and the steps for prevention. The research findings suggest that neighborhoods, as the closest administrative units to the community, need to adopt effective and responsive approaches and collaborate with local institutions to develop strategies and initiatives aimed at enhancing efforts to prevent violence against women and children.